Uterine leiomyoma-a common pathology with a rare life-threatening complication - Vihar, Nuzhath Backer Subi; Mani, Suja Mary; Wills, Vinitha; Mathew, Susan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Uterine leiomyoma, a common disease of women in reproductive age group may rarely present with a complication as an acute abdomen. We report such a case, a 40-year-old unmarried woman presented to our emergency department with acute abdominal pain, abdominal distension. Ultra sonogram abdomen revealed a large uterine leiomyoma causing small intestinal obstruction. The same was confirmed with abdominal imaging-X-ray erect and CECT. Managed by emergency exploratory laparotomy along with gastro surgical team. Small bowel obstructions are most commonly caused by postoperative adhesions, intestinal volvulus, malignancies or masses and strangulated hernias (together forming 90% of cases). The remaining are due to wide range of intrinsic and extrinsic bowel lesions. Small bowel obstruction is relatively a rare complication of uterine leiomyoma and occurring either as a result of compression of bowel loops by a large leiomyoma in the peritoneal cavity (as in this case), bowel loops incarceration between large pedunculated leiomyoma or bowel adhesions to the infarcted leiomyoma. Possibility of leiomyoma as the culprit causing intestinal obstruction to be considered especially in females with fibroid who present with an acute abdomen.